Pemanfaatan Fasilitas Media Intrenet Terhadap Hasil Belajar Siswa Di Kelas X Smks 1 Pembangunan Kota Bengkulu - setiawan, wawan (Journal Of Dehasen Educational Review, 2024)
The purpose of this study was to determine the utilization of internet media for learning logic concepts and algorithms in class X SMKS1 Pembangunan Bengkulu city. The method used in this research is descriptive qualitative method. The study found out the utilization of internet media learning logic concepts and algorithms in class X SMKN 1 Development Bengkulu city which amounted to 15 students. The data collection techniques used are Observation, Interview, The results of this study are to determine the utilization of internet media learning logic concepts and algorithms for the better and there is active participation from students learning which is more centered on practice and learning materials